(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to speech acts, which are considered one of the important branches of pragmatics, and their categories and classifications. Speech acts are considered as the basic unit of the communication system. The content of speech acts consists of a combination of linguistic and non-linguistic features. In our work, the history of the formation of speech acts, the opinions of linguists and philosophers who contributed to its development are described in detail. The types of speech acts are shown with the help of linguistic evidence taken from artistic texts